PENGARUH PROFITABILITAS, STRUKTUR ASET, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL (Students' Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of profitability, asset structure and growth in sales of capital structure in companies listed in Indonesia Stock Exchange (IDX) 2011-2013. The population in this study are all Manufacturing company located in IDX (Indonesia Stock Exchange) 2011-2013. The sampling technique was done by purposive sampling, sampling. Based on purposive sampling obtained a sample of 63 perusahaan. Teknik data analysis used is multiple linear regression analysis. Based on the test results it can be concluded that the variables negatively affect the profitability of capital structure, asset structure and the positive effect on sales growth capital structure. Keywords: profitability, assetstructure, sales growth and capital structure